2004
DOI: 10.1089/104454704774076208
|View full text |Cite
|
Sign up to set email alerts
|

Photobiological Basis and Clinical Role of Low-Intensity Lasers in Biology and Medicine

Abstract: The purpose of this article is to provide a comprehensive review on the clinical role of low intensity laser therapy (laser photostimulation) in biology and medicine. Studies on wound healing and pain relief are highlighted to show the clinical efficacy of laser therapy. Controversies about the use of low intensity laser as a therapeutic modality for wound healing and pain relief are presented and a brief explanation is provided to overcome these controversies. The importance of standard parameters is emphasiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
1
29

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 192 publications
(131 citation statements)
references
References 109 publications
2
99
1
29
Order By: Relevance
“…21 -23 According to Karu et al 17.24 and other authors [20][21][22][23] , exposure to LLLT stimulates an extra mitochondrial electrochemical activity and a simultaneous increase in the synthesis of adenosine triphosphate (ATP), in addition to an increase in the intracellular concentration of calcium (Ca +2 ), exerting effects on cellular signaling and increasing the activity of NOS in endothelial cells, which would offer cytoprotection to damage caused by lipid peroxidation induced by LLLT. [14][15][16] A B C D …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…21 -23 According to Karu et al 17.24 and other authors [20][21][22][23] , exposure to LLLT stimulates an extra mitochondrial electrochemical activity and a simultaneous increase in the synthesis of adenosine triphosphate (ATP), in addition to an increase in the intracellular concentration of calcium (Ca +2 ), exerting effects on cellular signaling and increasing the activity of NOS in endothelial cells, which would offer cytoprotection to damage caused by lipid peroxidation induced by LLLT. [14][15][16] A B C D …”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Previous studies in our laboratory as well as others have suggested that photo-stimulation by laser seems to occur during the inflammatory and proliferative phases of wound healing, exactly because of their influence on biomodulation of eicosanoids, especially PGs, and on the oxidative enzyme system of the skin. 1,2,5,[11][12][13][14][15][16][17][18][19] Consequently, studies that show the effects of combined treatments in wound healing are opportune, since both laser therapy and the use of COX inhibitors act during the same time period in the repair process, that is, both separate treatments affect the inflammatory and proliferative phases of skin healing in animals and humans. Considering this scenario, the purpose of this pre-clinical study was to evaluate the isolated and combined effects of low level laser therapy (LLLT) with helium-neon (He-Ne, 632nm) and selective inhibition of cyclooxygenase-2 (COX-2) in the reepithelialization of skin-incisional wounds in mice.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations